Dormindo com o Inimigo: Uma Crítica ao Conceito de Confiança - João Feres; José Eisenberg (Universidade do Estado do Rio de Janeiro, 2006)
In this article we intend to demonstrate that mainstream interpretations of international survey results on the value of interpersonal trust are often imprecise and mistaken, since they ignore the different roles conflict-adjudicating institutions play in mediating interpersonal relations in the societies the survey is applied, and thus the capacity this institutions have in fashioning civic and political cultures. Consequently, the answers obtained in public opinion polls referring to the concept of trust end up translating a very distinct dimension from that originally intended by those conducting the study. At the same time, the assumption that culture is an independent variable that determines social and political relations runs unchecked by the methodology and is confirmed in the final interpretation of results. In short, due to such analytical weakness, the concept of interpersonal trust is turned ineffective as a tool for empirical measurement, thus leading to erroneous nomological conclusions.